Multiphoton crosslinking for biocompatible 3D printing of type I collagen. (3rd September 2015) - Bell, Alex; Kofron, Matthew; Nistor, Vasile
Abstract: Multiphoton fabrication is a powerful technique for three-dimensional (3D) printing of structures at the microscale. Many polymers and proteins have been successfully structured and patterned using this method. Type I collagen comprises a large part of the extracellular matrix for most tissue types and is a widely used cellular scaffold material for tissue engineering. Current methods for creating collagen tissue scaffolds do not allow control of local geometry on a cellular scale. This means the environment experienced by cells may be made up of the native material but unrelated to native cellular-scale structure. In this study, we present a novel method to allow multiphoton crosslinking of type I collagen with flavin mononucleotide photosensitizer. The method detailed allows full 3D printing of crosslinked structures made from unmodified type I collagen and uses only demonstrated biocompatible materials. Resolution of 1 μ m for both standing lines and high-aspect ratio gaps between structures is demonstrated and complex 3D structures are fabricated. This study demonstrates a means for 3D printing with one of the most widely used tissue scaffold materials. High-resolution, 3D control of the fabrication of collagen scaffolds will facilitate higher fidelity recreation of the native extracellular environment for engineered tissues.